Skenario Pengembangan Sistem Pengelolaan Sampah Kabupaten Pasaman Barat dengan Pendekatan Skala Pengolahan Sampah di Tingkat Kawasan dan Kota - Rizki Aziz; Taufiq Ihsan; Ade Septia Permadani (Fakultas Teknik, 2019)
This study aims to analyze the existing conditions of the solid waste management system in Pasaman Barat Regency and discuss the alternative development of solid waste management systems with a solid waste treatment approach At the regional and municipal scale as a solution to the problem of solid waste management in Pasaman Barat Regency. From this study it is known that the level of existing solid waste management services was only 9.13% of total solid waste generated. The problems faced in solid waste management in Pasaman Barat Regency were still high levels of unserved solid waste, inadequate operational facilities and infrastructure for solid waste management, uneven handling of solid waste in service area coverage and the low practice of waste minimization and utilization. The solid waste man-agement system in Pasaman West Regency in the future can apply a combination of solid waste manage-ment approaches at the regional level based on Solid Waste Treatment Station with reduce-reuse-recycle approach (TPS 3R) in domestic areas and treatment at the city level based on Intergrated Solid Waste Treatment Station (TPST) at the landfill site, with the development of the system planned for 15 years, solid waste volume taken into the landfill site can be reduced by 22.40%